Giant H II regions in NGC 7479 and NGC 6070 - Firpo, Verónica (2010)
We present new results from our search for giant H II regions in galaxies visible from the Southern hemisphere. In this work we study two galaxies: NGC 7479 and NGC 6070. Using high-resolution spectra, obtained with different instruments at Las Campanas Observatory, we are able to resolve the emission-line profile widths and determine the intrinsic velocity dispersion of the ionized gas. We detect profile widths corresponding to supersonic velocity dispersions in the six observed H II regions. We find that all of them show at least two distinct kinematical components: a relatively narrow feature (between 11 and 22 km s-1) and a broader (between 31 and 77 km s-1) component. Two of the regions show a complex narrow profile in all ion lines, which can be further split into two components with different radial velocities. Whereas the wing broadening of the overall profile can be fitted with a low-intensity broad component for almost all profiles, in one region it was better reproduced by two separate shell-like wings. We have analysed the impact that the presence of multiple components has on the location of the H II regions in the log (L)-log (σ) plane. Although the overall distribution confirms the presence of a regression, the precise location of the regions in the plane is strongly dependent on the components derived from the profile fitting.